Effect of high-temperature severe plastic deformation on microstructure and mechanical properties of IF steel - Jindal V.; Rupa P.K.P.; Mandal G.K.; Srivastava V.C. (My University, 2025)
Extensive research work has been carried out on interstitial-free steel to understand its response to deformation; particularly, the behavior during severe plastic deformation (SPD). However, most of these studies were mainly undertaken in the ferritic regime. The present investigation reports the initial results of our attempt to employ accumulative roll bonding (ARB), one of the variants of SPD, at a high temperature (950 °C). A considerable grain refinement has been observed, which may be attributed to the severity of deformation and recrystallisation at high temperatures. Nanoindentation tests have been performed at various stages of ARB process to understand the evolution of mechanical properties. © ASM International.